PENGARUH PENERAPAN MODEL INDUKTIF TERHADAP HASIL BELAJAR BIOLOGI SISWA DI KELAS X MIPA SMA NEGERI 1 SUNGGUMINASA - Nurul Utami Halimsyah (Jurnal Biotek, 2017)
Inductive learning model is a learning model that has three phases, namely the formation of concepts, data interpretation and application of the principle. The influence of implementation inductive model in improving learning outcomes of grade X MIPA student at SMAN 1 Sungguminasa. The study is a quasi-experement with nonequivalent control group design. The population of the study was grade X MIPA students of the second semester of academic year 2016/2017 in SMAN 1 Sungguminasa. The results of the study reveal that the implementation of inductive model significant influence toward learning outcomes students.